Daily and weekly rest periods - MAJCHRZAK, KATARZYNA (Prawo Kanoniczne, 2014)
In the article issues of the daily and weekly rest periods of rest were addressed in the light of provisions of the labour law. The legislator in the Labour Code has implemented regulations that guarantee periods of rest. The employee is entitled to the time of rest in order to be able to effectively perform one's duties. Therefore during every twenty-four hours the employee has the right to at least 11 consecutive hours of the rest. However the weekly rest periods should include at least 35 hours, including at least 11 consecutive hours of daily rest period. If daily dimension of employee’s work amounts to at least 6 hours, then he is entitled to 15 minutes of the break included in working hours. Work performed in the overtime, extends working hours of the worker and therefore the legislator clearly determined conditions which must be fulfilled to use this institution. Overtime work should be compensated to an employee through additional remuneration of compensatory rest period. Working hours of young workers comparing to working hours of adult workers were shortened and adapted for their age and the young organism that needs more rest. Also a time of the learning is included in working hours of young workers therefore effectively their working hours are shorter than of remaining employees.